Excess — transgression — sanctity: analysis of St. Withelm’s life (according to The Lives of the Saints by Piotr Skarga) - Cybulska-Bohuszewicz, Ewa (Slavistica Vilnensis, 2019)
The paper presents an analysis of the life of St. Wilhelm. It is based on The Lives of the Saints (Żywoty świetych) by Piotr Skarga published in Vilnius in 1579. The article is a development of earlier findings and researches on the phenomenon of transgression in The Lives of the Saints [Cybulska-Bohuszewicz 2018, 13–36]. As tools of analysis, it uses the concepts developed by thinkers such as Georges Bataille, Józef Kozielecki and Victor Turner. The work is innovative, because so far The Lives of the Saints has not been studied in this way. At the same time, the sketch is only a contribution to further research, culminating in a monograph devoted to the issues of transgression, sanctity and atopy in the work mentioned.